Asuhan Keperawatan Terapi Relaksasi Otot Progresif Pada Lansia Hipertensi dengan Masalah Gangguan Rasa Nyaman - Tri Satria Ramadhan; Ria Wulandari; Fitri Afdhal; Ranida Arsi (JURNAL KESEHATAN TERAPAN, 2026)
Hypertension in the elderly can lead to serious complications such as stroke and heart failure. In addition topharmacological therapy, non-pharmacological interventions are needed to improve patient comfort, one of which isprogressive muscle relaxation therapy. This study aimed to determine the effectiveness of progressive muscle relaxation therapy in improving comfort among elderly patients with hypertension at Bhayangkara Moh. Hasan Hospital, Palembang.The research method used a descriptive case study design with two hypertensive patients. One patient received progressive muscle relaxation therapy for three days, while the other patient received only standard pharmacological therapy. Data werecollected through observation, interviews, and clinical records. Results showed that patients who underwent progressivemuscle relaxation therapy experienced increased comfort, better sleep, decreased headaches, and a blood pressure drop to120/80 mmHg. Meanwhile, patients who received only pharmacological therapy experienced partial improvement. Inconclusion, progressive muscle relaxation therapy is effective in improving comfort and stabilizing blood pressure, and is therefore recommended as a complementary intervention to pharmacological therapy in elderly hypertensive patients.